The Ameliorative Effects of Propolis against Cyclosporine A Induced Hepatotoxicity and Nephrotoxicity in Rats - Seven, Ismail; Gul Baykalir, Burcu; Tatli Seven, Pinar; Dagoglu, Gurdal (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
This study was planned to determine the effects of propolis in rats applied Cyclosporine A (CsA). In this study, 24 male Sprague-Dawley rats were used. Rats were randomly divided into 4 groups including control and 3 treatment groups. Group 1 (Control) were no supplement; CsA (group 2) were given as s.c. 15 mg/kg body weight (BW) every day; Propolis (group 3) were given by gavage 100 mg/kg BW every day; CsA+Propolis (group 4) were given as s.c. 15 mg/kg BW of CsA and by gavage 100 mg/kg BW of propolis every day. The feed intake were significantly higher (P<0.01) in Control and Propolis groups than CsA and CsA+Propolis groups within time period of 21 days. Further, body weight was significantly lower (P<0.01) in groups administrated with CsA (Group 2 and 4) than the other groups. Cortisol, AST, ALT and urea levels in serum of Control, Propolis and CsA+Propolis groups were found significantly lower (P<0.01) than those of CsA group. Malondialdehyde levels in kidney and liver tissues were significantly higher (P<0.01) than in the CsA groups compared to other groups. The catalase and reduced glutathione activities in kidney tissue of CsA+Propolis group were significantly higher (P<0.01) than those of CsA group. The present study demonstrated that propolis provided amelioration in terms of hepatotoxicity and nephrotoxicity consisting rats applied to CsA.
Ratlarda hepatotoksisite ve nefrotoksisite oluşturan siklosporin a'ya karsj propolisin iyileştirici etkileri
Keywords: Cyclosporine A (CsA); Propolis; Hepatotoxicity; Nephrotoxicity; Rat